Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation. (May 2023) - Searle, Kate R.; Regan, Charlotte E.; Perrow, Martin R.; Butler, Adam; Rindorf, Anna; Harris, Michael P.; Newell, Mark A.; Wanless, Sarah; Daunt, Francis
Abstract: Industrial forage fish fisheries may reduce prey availability affecting diet and breeding success of marine predators. However, evidence for fisheries effects on predator demography remains rare, hindering evaluation of their impact on populations. Using 25 years of data on the commercial lesser sandeel fishery in the north-western North Sea, we evaluated the effectiveness of the closure in safeguarding breeding success of four seabird species - black-legged kittiwake, common guillemot, Atlantic puffin and razorbill. We also tested for effects of a scientific fishery in the closed area on breeding success. We quantified how changes in the diet of chicks for the four seabird species were influenced by the abundance of sandeels and the alternative prey species, European sprat, and the potential prey behavioural disturbance effects of sandeel fishing on the prey. Finally, we examined how changes in chick diet and prey abundance have shaped long-term variation in seabird breeding success. The period of fishery operation was associated with a decline in kittiwake breeding success in colonies with foraging ranges overlapping the closed area, from 52 % of young fledged pre-fishery to 23 % during fishery operation. Breeding success increased by approximately 10 % in the period following fishery closure to 2018. We document wide uncertainty around this increase in breeding success, partly driven by variation in the responses of individual colonies. For guillemot, razorbill and puffin we found no evidence for negative effects of the fishery on breeding success, nor for positive effects arising from its closure. We found no evidence for an impact on breeding success of the scientific fishery. The proportion of sandeel in chick diet was positively associated with breeding success in the four species, albeit with only weak evidence for puffin. Fishing effort was associated with a decreased proportion of sandeel in puffin diet, a lower proportion of the sandeel component of the diet consisting of 0-group in kittiwake, razorbill and puffin, and with decreased kittiwake breeding success. Our findings provide quantitative evidence for how forage fish fisheries may impact seabird demography, highlighting the species-specific nature of responses, and the difficulties in teasing apart drivers amongst ongoing environmental change. Time-area fisheries closures show promise as a tool for positively affecting productivity in some seabird species. However, we identify important caveats around its effectiveness for strategic seabird conservation and aspirations of net gain.